Application of system dynamics to reveal the suitable CPFR mode and unsold goods return policy for deteriorating items. Issue 2 (17th February 2022) - Chen, Juin-Han; Yeh, Jun-Hsien; Chen, Ke-Chih
Abstract: With the intensification of global competition and rapid changes in customer needs, most companies focus on rapid customer response. This has caused problems such as shortened product lifecycles, diversified and small volume demands, and shortened lead time order. As a result, suppliers at all levels in a supply chain produce too many finished products, parts, or components, and increase inventory stock. This is an undesirable situation, particularly for deteriorating items. Increased inventory of deteriorating items does not only increase inventory cost, but also the product cost when the items lose function due to long storage time. In order to solve this problem, many scholars have proposed tools to improve supply chain performance, for example, collaborative planning, forecasting and replenishment (CPFR). Therefore, this research applied system dynamics to reveal the suitable CPFR mode for deteriorating items under two types of unsold goods return policies. The first model prohibits buyer to return unsold goods to seller, while the second model allows buyer to return unsold goods to seller. By using CPFR, buyer and seller can share, change and instantly update forecast information, both on the supply and demand sides. The inventory levels can be minimized and the bullwhip effect in supply chain can be resolved by CPFR to create a win-win situation for both seller and buyer. The results show that for deteriorating items, seller receives more profit than buyer in all four CPFR scenarios under the policy that buyer cannot return goods to seller. However, if buyer can return goods to seller, the seller's profit is less than the buyer's but the profit gap is not as wide as the previous model. Therefore, to maintain long-term collaborative relationship, seller should allow buyer to return goods. In both models, total profit is the highest when buyer is responsible for order generation in CPFR. This study applied system dynamics to illustrate the impact of different business models on supply chain performance and then to reveal effective strategy for supply chain partners.